Avaliação do financiamento da fruticultura, com ênfase na cultura da banana, na microrregião cearense do Baixo Jaguaribe (1998-2004): aspectos econômicos, sociais e tecnológicos - Barreto, Carlos Alberto Pinto de (2009)
The purpose of this dissertative work is to show the results of the implementation of the resources from the Programa de Apoio ao Desenvolvimento Rural do Nordeste (Rural), operated by the Banco do Nordeste do Brasil, flower-culture projects in districts of the Baixo do Jaguaribe Ceará´s microregion. This way, its main objective consists of evaluating the economic social and technological effects derived from the implementation of the mentioned program in interprisings of fruit-culture with emphasys in banana-culture in the districts of Limoeiro do Norte, Quixeré, São João do Jaguaribe and Tabuleiro do Norte, between 1998 and 2004. A study has been held considering the kind of evaluation named ex post, which is held after the accomplishment of the projects. Bibliographyc and documental researches have been held related to the theme. The investigative field work consisted of making structured interviews, making use of a set of closed questions directed to twenty one banana-curturers. The colected information was analysed based on statistic treatment giving a quantitative approach to the evaluative work. From the twenty-one banana-culturers, fifteen had their bussinesses completelly stopped, not promoting jobs or profits. These fifteen workers blamed, among other reasons, the electricity cut-off in the Altinho region, which is located in Tabuleiro do Norte. They also named some failures in the elaboration and administration of the projects in the area mentioned. Otherwise, six banana-culturers were normally developing their financed projects, developing financial and technological gains and promoting regular jobs. It´s important to mention that these six workers were not members of the Altinho region. Having as a parameter what was seen, we may say that the success and non-success of the agricultural investments consists on different aspects, being the rural credit only one of these aspects. The adequate conjugation of these aspects is what enables a bigger success in this kind of investiment. Therefore, the rural credit can not be considered the only or main responsible factor for the improvement of production and productivity, increase of technological levels, jobs and income in these areas of agricultural production.